Pengembangan E-Modul Berbasis Android pada Penggunaan Perkakas Tangan untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X TAV di SMKN 3 Surabaya - Rufus Setiyo Andrianto; Yulia Fransisca (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
In carrying out teaching and learning activities, of course learning media is needed that can support student learning. E-module is a learning media that contains images, videos and quizzes that can provide feedback in learning for students. This research focuses on developmente-mode basedandroid on the use of hand tools. Developmente-mode based android uses the ADDIE development model which has several stages, namelyanalysis, design, development, implementation, andevaluation. This research uses a research designone group pretest-posttest. The subjects of this research were class X TAV SMKN 3 Surabaya with 32 students. Validation is carried out to measure feasibilitye-mode. Student responses are needed to measure practicalitye-mode during learning. Student learning outcomes in the knowledge domain and skills domain are analyzed using the T test to measure effectivenesse-mode in learning. The research results show that (1) the validity of the developmente-mode obtained a result of 83.89% with very valid criteria, which means it is very suitable for use in learning. (2) practicalitye-mode which was developed obtained student response results of 89.47% with very practical criteria, which meanse-modebased android very practical for use in learning to use hand tools. (3) effectivenesse-mode obtained from learning results in the knowledge domain and the attitude domain. In the knowledge domain, the average value is obtainedpre-test of 48.9, while the average valuepost-test amounted to 87.91, and the T test significance value was 0.000<0.05. In the skills domain, an average skill value of 91.92 was obtained, greater than the KKM value of 75, and a T test significance value of 0.000<0.05 was obtained. It can be concluded that there is a significant increase in student learning outcomes in the realm of knowledge and skills.